Pre- and postconditioning effect of Sevoflurane on myocardial dysfunction after cardiopulmonary resuscitation in rats - Knapp, Jürgen; Bergmann, Greta; Bruckner, Thomas; Russ, Nicolai; Böttiger, Bernd W.; Popp, Erik (Resuscitation, 2013)
Post-resuscitation myocardial dysfunction is an important cause of death in the intensive care unit after initially successful cardiopulmonary resuscitation (CPR) of pre-hospital cardiac arrest (CA) patients. Volatile anaesthetics reduce ischaemic-reperfusion injury in regional ischaemia in beating hearts. This effect, called anaesthetic-induced pre- or postconditioning, can be shown when the volatile anaesthetic is given either before regional ischaemia or in the reperfusion phase. However, up to now, little data exist for volatile anaesthetics after global ischaemia due to CA. Therefore, the goal of this study was to clarify whether Sevoflurane improves post-resuscitation myocardial dysfunction after CA in rats. Following institutional approval by the Governmental Animal Care Committee, 144 male Wistar rats (341±19g) were randomized either to a control group or to one of the 9 interventional groups receiving 0.25 MAC, 0.5 MAC or 1 MAC of Sevoflurane for 5min either before resuscitation (SBR), during resuscitation (SDR) or after resuscitation (SAR). After 6min of electrically induced ventricular fibrillation CPR was performed. Before CA (baseline) as well as 1h and 24h after restoration of spontaneous circulation (ROSC), continuous measurement of ejection fraction (EF), and preload adjusted maximum power (PAMP) as primary outcome parameters and end systolic pressure (ESP), end diastolic volume (EDV) and maximal slope of systolic pressure increment (dP/dtmax) as secondary outcome parameters was performed using a conductance catheter. EF was improved in all Sevoflurane treated groups 1h after ROSC in comparison to control, except for the 0.25 MAC SDR and 0.25 MAC SAR group (0.25 MAC SBR: 38±8, p=0.02; 0.5 MAC SBR: 39±7, p=0.04; 1 MAC SBR: 40±6, p=0.007; 0.5 MAC SDR: 38±7, p=0.02; 1 MAC SDR: 40±6, p=0.006; 0.5 MAC SAR: 39±6, p=0.01; 1 MAC SAR: 39±6, p=0.002, vs. 30±7%). Twenty-four hours after ROSC, EF was higher than control in all interventional groups (p<0.05 for all groups). EF recovered to baseline values 24h after ROSC in all SBR and SAR groups. PAMP was improved in comparison to control (4.6±3.0mW/μl2) 24h after ROSC in 0.5 MAC SBR (9.4±6.9mW/μl2, p=0.04), 1 MAC SBR (8.9±4.4mW/μl2, p=0.04), 1 MAC SDR (8.0±5.7mW/μl2, p=0.04), and 1 MAC SAR (7.3±3.5mW/μl2, p=0.04). ESP, EDV, and dP/dtmax was not different from control 1h as well as 24h after ROSC with the exception of 1 MAC SDR with a reduced ESP 1h after ROSC (89±16 vs. 103±22mmHg, p=0.04). Sevoflurane treatment did not affect survival rate. This animal study of CA and resuscitation provides the hypothesis that pharmacological pre- or postconditioning with the volatile anaesthetic Sevoflurane - administered before CA, during resuscitation or after ROSC - results in an improved myocardial inotropy 24h after ROSC. Sevoflurane treatment seems to improve EF even in the early phase of reperfusion 1h after ROSC. Therefore further targeted studies on the optimal dose and time point of administration of Sevoflurane in cardiopulmonary resuscitation seem to be worthwhile (Institutional protocol number: 35-9185.81/G-24/08).
Gesehen am 07.06.2022